Value of extent of hippocampal resection in the surgical treatment of temporal lobe epilepsy - Leonardo Bonilha; Eliane Kobayashi; João Paulo V. Mattos; Donizete C. Honorato; Li M. Li; Fernando Cendes (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: Unilateral hippocampal atrophy is indicator of good surgical prognosis in patients with temporal lobe epilepsy (TLE). Some patients however do not become seizure free after surgery. We assessed if the extent of hippocampal and amygdala resection is associated with outcome. METHODS: Thirty patients with TLE with unilateral or clearly asymmetric hippocampal atrophy who underwent surgical treatment were evaluated concerning preoperative clinical variables and interictal EEG abnormalities. Amygdala and hippocampal resection was evaluated by post-operative MRI. We compared seizure free versus non-seizure free patients, and patients with good outcome (Engel's classes I and II) versus patients with poor outcome. RESULTS: There was significant association between the extent of hippocampal resection and the outcome. Pre-operative variables and interictal EEG abnormalities did not show relationship with outcome as documented in previous studies. CONCLUSION: The extent of hippocampal resection is associated with outcome. Incomplete resection of atrophic hippocampus may explain most surgical failures in patients with TLE due to unilateral hippocampal sclerosis.